Clays and Clay Minerals, Vol. 57, No. 3, 302–310, 2009. - Mantovani, Marco; Escudero, Alberto; Becerro, Ana Isabel (My University, 2009)
Understanding the mechanisms for illitization of clay minerals has important applications in reconstructing geologic histories and determining the origins of physical and chemical characteristics of buried sediments. While many studies have been carried out on this topic, few have focused on the mechanism of illite formation from kaolinite. The purpose of this study was to investigate more deeply the illitization of kaolinite in KOH solution at a high solid/liquid ratio (1000 mg/mL). X-ray diffraction (XRD) and infrared spectroscopy were used to follow the formation of new crystalline phases and the composition of the octahedral sheet, while the transformation of the Si and Al local environments was analyzed by 29Si and 27Al magic angle spinning nuclear magnetic resonance spectroscopy (MAS NMR). The results revealed that the first reaction stage consists of the diffusion of Al from the octahedral to the tetrahedral sheet of the kaolinite TO layers, giving rise to the precursors of the illite/muscovite nuclei. Combination of XRD with 27Al MAS NMR measurements indicated that a minimum amount of tetrahedral Al is required in the original TO layer before condensation of a second tetrahedral sheet occurs to complete the formation of the illite/muscovite TOT layers.
Application Of 29si And 27al Mas Nmr Spectroscopy To The Study Of The Reaction Mechanism Of Kaolinite To Illite/muscovite
gsccm57303-man.pdf: 328KB
Keywords: Periodicals; Geology; Al-27 MAS NMR; Hydrothermal Experiments; Illite; IR Spectroscopy; Kaolinite; Muscovite; Si-29 MAS NMR; X-ray Diffraction